2003
DOI: 10.1021/bp025589f
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell Cycle for Enhancement of Antibody Productivity in Perfusion Culture of NS0 Cells

Abstract: A prolonged period of high productivity at high cell density is desirable for industrial production of biopharmaceuticals. Previous efforts have shown that cessation of cell proliferation in low cell density culture results in increased productivity. We report here further results on multigenic manipulation of cell cycle and apoptosis to enhance productivity at high cell density. The NS0 6A1/4-9F myeloma cell line, which constitutively expresses a chimeric IgG4 antibody and inducibly expresses the p21(CIP1) cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 31 publications
3
33
0
1
Order By: Relevance
“…In growth-controlled cells, recombinant gene expression was enhanced. In fact, many of the previous investigations of unrelated proliferationcontrol systems in a biotechnological context have found an increased productivity (per cell) during growth arrest Ibarra et al 2003;Bi et al 2004). This is in accordance with the notion that growth-controlled producer cells devote more resources to recombinant protein production.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In growth-controlled cells, recombinant gene expression was enhanced. In fact, many of the previous investigations of unrelated proliferationcontrol systems in a biotechnological context have found an increased productivity (per cell) during growth arrest Ibarra et al 2003;Bi et al 2004). This is in accordance with the notion that growth-controlled producer cells devote more resources to recombinant protein production.…”
Section: Discussionsupporting
confidence: 82%
“…Various attempts have been made to establish such a proliferation-controlled producer cell line, however, despite much progress to meet all of the multiple and complex requirements of an industrial production process, no such system has yet been developed to the stage of a commercial application (Geserick et al 2000;Meents et al 2002a, b;Watanabe et al 2002;Chilov et al 2003;Ibarra et al 2003;Bi et al 2004; for a review see Fussenegger et al 1999). In these approaches, growth-control systems were superimposed on established cell lines that have previously been selected extensively to achieve maximal growth rates and that have lost the endogenous cell growth-control mechanisms of primary cells.…”
Section: Introductionmentioning
confidence: 99%
“…Protein production is dependent on the phase of the cell-cycle and several genes such as those involved in ribosome biogenesis and protein translation are expressed highly in the G1 phase (Al-Rubeai and Emery 1990;Al-Rubeai et al 1992;Moore et al 1997;Fussenegger et al 1998Fussenegger et al , 2000Kaufman et al 1999Kaufman et al , 2001Carvalhal et al 2003;Ibarra et al 2003;Yoon et al 2003a, b;Fogolin et al 2004;Bi et al 2004;Trummer et al 2006). Cells arrested at the end of G1-phase of cell cycle are metabolically more active and bigger in size than non-arrested cells (Carvalhal et al 2003;Bi et al 2004).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 99%
“…Cells arrested at the end of G1-phase of cell cycle are metabolically more active and bigger in size than non-arrested cells (Carvalhal et al 2003;Bi et al 2004). For these reasons, the G1-phase of the cell cycle is considered the ideal time for increased production of recombinant proteins and G1 arrest has been used to increase the productivity in a number of commercially relevant cell lines such as hybridomas and CHO (Al-Rubeai and Emery 1990;Al-Rubeai et al 1992;Moore et al 1997;Fussenegger et al 1998Fussenegger et al , 2000Kaufman et al 1999Kaufman et al , 2001Ibarra et al 2003;Yoon et al 2003a, b;Fogolin et al 2004;Trummer et al 2006). Some studies have reported the S phase as the optimal production phase (Lloyd et al 2000;Fox et al 2005), an example being the increased production of human interferon-c (IFN-c) upon increasing the percentage of CHO in S phase (Fox et al 2005).…”
Section: The Use Of Cell Cycle Arrest To Increase Recombinant Proteinmentioning
confidence: 99%
“…An additional optimization strategy would be prevention of the onset of apoptosis after cessation of growth, at which time cells are accumulating in the G1 cell cycle phase. Identification of regulatory mechanisms for cell cycle progression and of associated environmental manipulation are emerging areas of research (Balcarcel and Stephanopoulos 2001;Bjorklund et al 2006;Carvalhal et al 2003;deZengotita et al 2001;Ibarra et al 2003;Sun et al 2004;Sunstrom et al 2000).…”
Section: Recombinant Protein Productivity As a Function Of Cell Cyclementioning
confidence: 99%